Venom of the Endoparasitoid Wasp Pteromalus puparum: An Overview - Jia-Ying Zhu; Gong-Yin Ye; Cui Hu (Psyche: A Journal of Entomology)
Parasitoid venom is a focal research point in the biological control area, which aims to explore its physiological functions and nature. Pteromalus puparum is a gregarious pupal endoparasitoid wasp which has evolved unique means to adopt the host's immune system, as no other parasitoid-associated factors other than venom are injected into its hosts during oviposition. It represents an excellent model for research of parasitoid venom. In this paper, information was gathered on outcomes of P. puparum venom. We first began this paper by examining its functional properties. Next, we reviewed the nature of this parasitoid's venom components. Even great achievements have been made, further research is required to uncover the sophisticated bioactivity of the venom and isolate more novel toxic peptides/proteins.